A Dual Resource Constrained Unrelated Parallel Machine Scheduling Model Considering Tardiness and Workload Balance - Larasati, Karina Amanda; Sukoyo, Sukoyo; Akbar, Muhammad (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2024)
The proposed study pertains to Multi-Task Simultaneous Supervision Dual Resource Constrained (MTSSDRC), which considers minimizing tardiness and workload balance. The workload balance is calculated using the Workload Smoothness Index (WSI). Additionally, the research concentrates on unrelated parallel machine schedules as they reflect the actual industry conditions in practice. This issue employs three methodologies: Mixed-Integer Linear Programming (MILP), Mixed-Integer Quadratic Problem (MIQP), and Mixed-Integer Quadratically Constrained Programming (MIQCP).  The results in the MILP model focus on the value of total tardiness so that the results obtained have a smaller total tardiness value. However, it is still uncertain that the WSI value is better because no boundaries have been set between the two objective functions to achieve optimal values in the MILP model. The MIQP model focuses on the Workload Smoothness Index (WSI) value to give a limit to the total tardiness objective function. Limit values ​​are obtained from MILP model values, and the resulting WSI value becomes smaller. Moreover, the MIQCP model focuses on the total tardiness value and has limits in the form of permitted WSI. This model produces a small WSI value in accordance with the specified WSI limits while adjusting the specified total tardiness.